Managerial economics : n - Keat, Paul G. 4 0 16; Young, Philip K.Y.; 5 (Upper Saddle River, N.J. : Pearson Education International, 2009)
Providing a learning environment by integrating a running case study and along with a capstone case, this text is for managerial economics courses taught in business schools and economics departments.
Pearson International edition -- Cover.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Managerial economics; 20; 2